Synchronous Paleo-Tethys closure in northern Iran: Constraints from Paleozoic-Mesozoic sediments in the western Alborz - Yiyang Lei; Yang Chu; Mark B. Allen; Wei Lin; Bo Wan; Ling Chen; Morteza Talebian; Guangyao Xin; Tanjie Liu; Yilin Guo; Lin Guo; Ranran Xia (Journal of Asian Earth Sciences, 2026)

Understanding variation in sustainable development goal relationships across spatial scales matters for making consistent priorities - Kai Wu; Junze Zhang; Prajal Pradhan; Cameron Allen; Min Cao; Jian Lin; Zhongchang Sun; Zheng Hu; Ya Tian; Guonian Lü; Huadong Guo; Bojie Fu; et al. (Sustainable Production and Consumption, 2026)

Cradle-to-gate carbon footprint of industrial-scale fermentative production of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) - Hsien-Tse Chen; Yu-Hsiang He; Pei-Yi Lin; Wei-Shu Huang; Kaarmukhilnilavan R. Srinivasan; Jun-You You; Pei-Yu Sun; Allen H. Hu; Penjit Srinophakun; Maythee Saisriyoot; Si-Yu Li (Journal of Cleaner Production, 2025)

Mapping dynamics of large-scale high-precision pond datasets using a semi-automated method based on deep learning - Zhenbang Hao; Lili Lin; Christopher J. Post; Elena A. Mikhailova; Jeffery Allen (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Decoupling of bacterial production and respiration in the surface water of the North Pacific Subtropical Gyre - Yuchen Zhang; Yibin Huang; Feipeng Xu; Shujie Cai; Yao Liu; Chao Xu; Lizhen Lin; Jixin Chen; Edward Allen Laws; Xin Liu; Bangqin Huang (Marine Life Science & Technology, 2025)
Heterotrophic bacterial production and respiration, two important contributors to carbon cycling, play an important role in global biogeochemical cycles. However, recent research suggests that these two processes may be decoupled, and the underlying changes in community structure and their interactions remain unclear. In this study, two research expeditions to the North Pacific Subtropical Gyre (NPSG) during the summer and winter of 2020–2021 revealed seasonal shifts in bacterial metabolism and community structure in response to environmental factors. The findings indicated notable seasonal fluctuations in bacterial abundance and production in the surface waters. Both peaked in winter compared to summer. Alterations in bacterial abundance that were further evident at the community level demonstrated significant seasonal differences in bacterial community structure and diversity and revealed, in particular, the intricacy of the networks and interactions among bacterial communities in winter. Bacterial respiration displayed no significant seasonal variations and was decoupled from bacterial abundance and production. The implication was that bacterial production did not directly dictate bacterial respiration. Specific taxa exerted a more substantial influence on bacterial respiration, potentially including groups with high respiration rates but relatively low abundance, thus challenging the notion that highly abundant taxa are invariably the most metabolically active. Moreover, the interplay between different bacterial taxa and their interactions may also impact the overall strength of bacterial community respiration. These findings significantly enhance our understanding of the decoupling between bacterial production and respiration, which is crucial for unraveling the complex mechanisms underlying carbon cycling and energy flow in marine ecosystems.

Nutrient recovery from high-salinity dairy wastewater through the cultivation of acclimatized microalgae - Rui Xiao; Erika Carter; Austin Allen; Pei-Lin Tan; Yu-Hua Zheng; Qian Chen; Shun-Ni Zhu; Sudeep C. Popat; Allan Knopf; Clinton F. Williams; Howard H. Chou; Huan Chen (Journal of Water Process Engineering, 2025)

Genetic patchiness of the endangered giant clam Tridacna maxima from Peninsular Malaysia - Li Keat Lee; Ya Yi Huang; Chaolun Allen Chen; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Po Teen Lim; Chui Pin Leaw (Coral Reefs, 2025)

Natural shading is helpful but not sufficient for mitigating warming in green sea turtle nests in the tropical South China Sea - Tsung-Han Liu; Ming-Shiou Jeng; Chan-Yuan David Lee; Chih-Wei Tu; Po-Hsiung Lin; Chaolun Allen Chen; Chia-Ying Ko (Biological Conservation, 2024)

A streamlined method to generate endothelial cells from human pluripotent stem cells via transient doxycycline-inducible ETV2 activation - Allen Chilun Luo; Jiuhai Wang; Kai Wang; Yonglin Zhu; Liyan Gong; Umji Lee; Xiang Li; Daniel M. Tremmel; Ruei-Zeng Lin; Donald E. Ingber; James Gorman; Juan M. Melero-Martin (Angiogenesis, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Vanishing giants: An assessment on the population status of giant clams across Malaysia - Li Keat Lee; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Chaolun Allen Chen; Po Teen Lim; Chui Pin Leaw (Regional Studies in Marine Science, 2024)

A Multiplex Assay to Simultaneously Monitor Apoptosis and Necrosis Using the Cellaca® PLX Image Cytometer - Mackenzie Pierce; Yongyang Huang; Allen Lin; Carolina Franco Nitta; Dmitry Kuksin; Bo Lin; Leo Li-Ying Chan (Journal of Fluorescence, 2024)

New depth record for oval squid, Sepioteuthis lessoniana, egg capsules in a mesophotic coral ecosystem natural habitat - Chao-Yang Kuo; Chun-Yen Lin; Ming-Jay Ho; Chaolun Allen Chen (Marine Biodiversity, 2023)

Cover Image - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)

Exogenous polyunsaturated fatty acids ( PUFAs ) influence permeability, antimicrobial peptide resistance, biofilm formation and membrane phospholipid structure in an A‐layer and non‐A ‐layer strain of Aeromonas salmonicida - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)
Aeromonas salmonicida is a Gram‐negative bacterium that can infect a wide host range of fish populations, including salmonids and non‐salmonids as well as freshwater and marine life. Some strains of A. salmonicida cause the disease furunculosis, which can cause lethargy, intestinal inflammation, ulcers, haemorrhaging and death. The infection is spread through fish‐to‐fish contact, and the presence of infection can have devastating effects on cultivated fish populations. The purpose of this study was to explore the ability of non‐A‐layer and A‐layer A. salmonicida strains to incorporate polyunsaturated fatty acids (PUFAs) into their lipid profile and test the phenotypic effects thereof. Lipids were extracted from PUFA‐exposed cultures and analysed for lipid modification by thin‐layer chromatography and ultraperformance liquid chromatography‐mass spectrometry, showing A. salmonicida , regardless of A‐layer, capable of incorporating all seven of the PUFAs studied. Phenotypic effects were determined through the use of assays that tested for biofilm formation, membrane permeability and cyclic peptide susceptibility. Temperature‐dependent effects on biofilm formation were observed, and PUFA exposure showed significant ( p

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Historical Connectivity and Demography of the Ferocious Reef Crab, Eriphia ferox (Crustacea; Eriphiidae), Demonstrate That Taoyuan Algal Reef Is an Essential Population Source Along the East Taiwan Strait - Mu-Han Chen; Ya-Yi Huang; Bi-Ying Huang; Hernyi Justin Hsieh; Jen Nie Lee; Mei Lin Neo; Hironobu Fukami; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The east Taiwan Strait is largely fringed by sandy and muddy habitats. However, a massive algal reef made of crustose coralline algae has been found along the coast off Taoyuan city in northwestern Taiwan. The porous structure of Taoyuan Algal Reef harbors high abundance and diversity in marine organisms, including the ferocious reef crab, Eriphia ferox . Such a pivotal geographic location and unique ecological features make Taoyuan Algal Reef a potential stepping stone connecting biotic reefs in the east Taiwan Strait, South China Sea to the south, and even the high latitude of Japan to the north. In this study, we examined the population connectivity and historical demography of E. ferox by analyzing mitochondrial cytochrome oxidase I (COI) fragments of 317 individuals sampled from 21 localities in the northwestern Pacific. Our analyses of haplotype network and pairwise F ST comparisons revealed a lack of phylogeographical structure among E. ferox populations, implying the existence of a migration corridor connecting the South and East China Seas through the east Taiwan Strait. Multiple lines of evidence, including significant values in neutrality tests, unimodally shaped mismatch distributions, and Bayesian skyline plots elucidated the rapid population growth of E. ferox following the sea-level rise after Last Glacial Maximum (ca. 2–10 Ka). Such demographic expansion in E. ferox coincided with the time when Taoyuan Algal Reef started to build up around 7,500 years ago. Coalescent migration analyses further indicated that the large and continuous E. ferox population exclusively found in Datan Algal Reef, the heart of Taoyuan Algal Reef, was a source population exporting migrants both northward and southward to the adjacent populations. The bidirectional gene flow should be attributed to larval dispersal by ocean currents and secondary contact due to historical population expansion. Instead of serving as a stepping stone, our results support that Taoyuan Algal Reef is an essential population source for biotic reef-associated species along the east Taiwan Strait, and highlight the importance of conserving such a unique ecosystem currently threatened by anthropogenic development.

Scleractinian diversity in the upper mesophotic zone of Ludao (Taiwan): a museum collection with new records from Taiwanese waters - Stéphane De Palmas; Vianney Denis; Derek Soto; Yuting Vicky Lin; Ming-Jay Ho; Chaolun Allen Chen (Marine Biodiversity, 2021)

A Millifluidic Perfusion Cassette for Studying the Pathogenesis of Enteric Infections Using Ex-Vivo Organoids - Reid L. Wilson; Sarah A. Hewes; Anubama Rajan; Shih-Ching Lin; Carolyn Bomidi; Takanori Iida; Mary K. Estes; Anthony W. Maresso; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2021)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Evaluation of cortisol and telomere length measurements in ethnically diverse women with breast cancer using culturally sensitive methods - Julio Ramirez; May Elmofty; Esperanza Castillo; Mindy DeRouen; Salma Shariff-Marco; Laura Allen; Scarlett Lin Gomez; Anna María Nápoles; Leticia Márquez-Magaña (Journal of Community Genetics, 2017)

The transient potassium outward current has different roles in modulating the pyloric and gastric mill rhythms in the stomatogastric ganglion - Lin Zhu; Allen I. Selverston; Joseph Ayers (Journal of Comparative Physiology A, 2017)

Recent declines in cancer incidence: related to the Great Recession? - Scarlett Lin Gomez; Alison J. Canchola; David O. Nelson; Theresa H. M. Keegan; Christina A. Clarke; Iona Cheng; Salma Shariff-Marco; Mindy DeRouen; Ralph Catalano; William A. Satariano; Kathleen Davidson-Allen; Sally L. Glaser (Cancer Causes & Control, 2017)

Examining the Neural and Astroglial Protective Effects of Cellular Prion Protein Expression and Cell Death Protease Inhibition in Mouse Cerebrocortical Mixed Cultures - Kevin K. W. Wang; Zhihui Yang; Allen Chiu; Fan Lin; Richard Rubenstein (Molecular Neurobiology, 2016)

Isolation of Functional Human Endothelial Cells from Small Volumes of Umbilical Cord Blood - Sa Do Kang; Tim A. Carlon; Alexandra E. Jantzen; Fu-Hsiung Lin; Melissa M. Ley; Jason D. Allen; Thomas V. Stabler; N. Rebecca Haley; George A. Truskey; Hardean E. Achneck (Annals of Biomedical Engineering, 2013)

Fabrication and Mechanical Evaluation of Anatomically-Inspired Quasilaminate Hydrogel Structures with Layer-Specific Formulations - Hubert Tseng; Maude L. Cuchiara; Christopher A. Durst; Michael P. Cuchiara; Chris J. Lin; Jennifer L. West; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2013)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

A note on reviving the Goddard Satellite-based Surface Turbulent Fluxes (GSSTF) dataset - Chung-Lin Shie; Long S. Chiu; Robert Adler; Eric Nelkin; I. -I. Lin; Pingping Xie; Feng-Chin Wang; R. Chokngamwong; William Olson; D. Allen Chu (Advances in Atmospheric Sciences, 2009)

An Atlas of ShakeMaps and population exposure catalog for earthquake loss modeling - Trevor I. Allen; David J. Wald; Paul S. Earle; Kristin D. Marano; Alicia J. Hotovec; Kuowan Lin; Michael G. Hearne (Bulletin of Earthquake Engineering, 2009)

Analysis of Acropora muricata Calmodulin (CaM) Indicates That Scleractinian Corals Possess the Ancestral Exon/Intron Organization of the Eumetazoan CaM Gene - Chih-Yung Chiou; I-Ping Chen; Chienhsun Chen; Henry Ju-Lin Wu; Nuwei Vivian Wei; Carden C. Wallace; Chaolun Allen Chen (Journal of Molecular Evolution, 2008)

Thiopurine S-methyltransferase activity in three major Asian populations: a population-based study in Singapore - Shirley Kow Yin Kham; Chin Kok Soh; Te Chih Liu; Yiong Huak Chan; Hany Ariffin; Poh Lin Tan; Allen Eng Juh Yeoh (European Journal of Clinical Pharmacology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Copper‐dependent iron transport in coastal and oceanic diatoms - Maria T. Maldonado; Andrew E. Allen; Joanne S. Chong; Kevin Lin; Dan Leus; Nataliya Karpenko; Shannon L. Harris (Limnology and Oceanography, 2006)
We investigated the presence of plasmalemma‐bound copper‐containing oxidases associated with the inducible iron (Fe) transport system in two diatoms of the genus Thalassiosira . Under Fe‐limiting conditions, Thalassiosira oceanica , an oceanic isolate, was able to enzymatically oxidize inorganic Fe(II) extracellularly. This oxidase activity was dependent on copper (Cu) availability and diminished by exposure to a multi‐Cu oxidase (MCO) inhibitor. The rates of Fe uptake from ferrioxamine B by Fe‐limited T. oceanica were also dependent on Cu availability in the growth media. The effects of Cu limitation on Fe(II) oxidation and Fe uptake from ferrioxamine B were partially reversed after a short exposure to a Cu addition, indicating that the putative oxidases contain Cu. Limited physiological experiments were also performed with the coastal diatom Thalassiosira pseudonana and provided some evidence for putative Cu‐containing oxidases in the high‐affinity Fe transport system of this isolate. To support these preliminary physiological data, we searched the newly available T. pseudonan a genome for a multi‐Cu‐containing oxidase gene and, using real‐time polymerase chain reaction (PCR), quantified its expression under various Fe and Cu levels. We identified a putative MCO gene with predicted transmembrane domains and found that transcription levels of this gene were significantly elevated in Fe‐limited cells relative to Fe‐replete cells. These data collectively suggest that putative MCOs are part of the inducible Fe transport system of Fe‐limited diatoms, which act to oxidize Fe(II) following reductive dissociation of Fe(III) from strong organic complexes.

Developmentally regulated expression of the P2X3 receptor in the mouse cochlea - Lin-Chien Huang; Allen F. Ryan; Debra A. Cockayne; Gary D. Housley (Histochemistry and Cell Biology, 2006)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Effects of recombinant lysostaphin on cytotoxicity and interleukin-8 level in normal human epidermal keratinocytes cell line - Err-Cheng Chan; C. Allen Chang; Tzong-Zeng Wu; Yuh-Ling Lin (Biotechnology Letters, 1998)

Acute hepatotoxicity of a tetrachlorobiphenyl?Changes in the hepatocyte ultrastructure and plasma membrane-bound enzymes - F. S. Lin; M. T. Hsia; J. R. Allen (Archives of Environmental Contamination and Toxicology, 1979)